(untitled) (El-Wahat Journal for Research and Studies, 2021)
The Aim Of This Study Is To See The Importance Of The Effect When Enabling The Staff Of The Administrative Creativity From The Points Of View Of The University Of Ghardaia Employees . And To Achieve The Goals Of The Study, A Questionnaire Comprising Of 27 Expressions Over A Sample Containing 100 Employees. The Study Adopted, When Analyzing The Questionnaire Data, The Statistical Package Of Social Sciences (SPSS) And To Test The Hypotheses, Some Statistical Methods Were Applied Some Of Which Were The Simple And The Gradual Gradient. The Study Came Up With The Existence Of The Dimension Empowerment Concerning The Participation In The Decisions And The Administrative Creativity Dependability. And No Trace Of Existence Of The Dimension Empowerment Concerning The Independence And The Discretion Or Any Stimulus For The Administrative Creativity . The Most Important Point The Study Came Up With Was The Necessity Of Granting The Employees The Independence And A Wider Space Of Discretion When Performing Business And The Importance Of Stimulation Materially And Morally To Encourage The Employees Devising New Ideas And Original Creativity. Key Words- Enabling The Employees, Independence, Discretion, Stimulus, Administrative Creativity.